Sending children to school 'back home': multiple moralities of Punjabi Sikh parents in Britain - Qureshi, K (Routledge, 2014)
This paper explores how Punjabi Sikh parents in Britain try to produce ‘good children’ through moral reasoning about their schooling. Parents compare schooling in Britain with India and wonder about sending their children to school ‘back home’, in the hope of immersing them in Indian culture, traditions and language. Whilst parents hope for cultural and religious gains for their children, this paper considers the discrepancies between the hopes and realities of sending children to school ‘back home’. The ethnographic material comes from a study of Indian Punjabi transnationalism involving fieldwork in the West Midlands and 72 interviews with parents, grandparents and young people. I first explore the views of parents and grandparents who promote the decision to send children to school in India. Then, focussing on two mothers, I explore the moral dilemmas that resulted from sending their children ‘back home’ and trace the contours of multiple moralities which come together, but ultimately pull into different directions. The paper demonstrates the value of Zigon’s theories on moral pluralism, and explores how the detail is held in the dynamics of gender, generation and class.